1994
DOI: 10.1002/anxi.3070010105
|View full text |Cite
|
Sign up to set email alerts
|

Safety signals and human anxiety: A fear‐potentiated startle study

Abstract: The effect of a safety signal on the magnitude of anticipatory anxiety was investigated using the fear-potentiated startle reflex paradigm in humans. The amplitude of the acoustic startle reflex was measured during the anticipation of unpleasant electric shocks ("threat") and during "safe" conditions. Threat and safe conditions were signaled by three different colored lights. Two lights signaled safe conditions (safe 1, safe 2) and the other light signaled the threat condition (threat). In phase I, the lights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…There is abundant evidence that knowledge of the CS–US contingency alone, in the absence of pairing of the CS and US and fear conditioning, can result in a physiological fear response that is almost identical to conditioned fear (see Olsson and Phelps, 2007, for a review). This episodic memory top-down driven fear response has been most frequently observed as measured with potentiated startle (Grillon et al, 1991, 1994; Funayama et al, 2001), but has also been observed with SCR (Phelps et al, 2001). Interestingly, although the acquisition and storage of explicit knowledge of the CS–US contingency does not depend on the amygdala (Bechara et al, 1995; LaBar et al, 1995), the physiological expression of this fear representation is amygdala-dependent (Funayama et al, 2001).…”
Section: The Current State Of Human Reconsolidationmentioning
confidence: 86%
“…There is abundant evidence that knowledge of the CS–US contingency alone, in the absence of pairing of the CS and US and fear conditioning, can result in a physiological fear response that is almost identical to conditioned fear (see Olsson and Phelps, 2007, for a review). This episodic memory top-down driven fear response has been most frequently observed as measured with potentiated startle (Grillon et al, 1991, 1994; Funayama et al, 2001), but has also been observed with SCR (Phelps et al, 2001). Interestingly, although the acquisition and storage of explicit knowledge of the CS–US contingency does not depend on the amygdala (Bechara et al, 1995; LaBar et al, 1995), the physiological expression of this fear representation is amygdala-dependent (Funayama et al, 2001).…”
Section: The Current State Of Human Reconsolidationmentioning
confidence: 86%
“…As is the case for experimental research with animal models, learned safety is only beginning to be explored in humans (Grillon and Ameli, 2001;Grillon et al, 1994b;Jovanovic et al, 2010Jovanovic et al, , 2012bLissek et al, 2009;Pollak et al, 2010b;Schiller et al, 2008). Already in the 1990s, pioneering work by Christian Grillon and Michael Davis firstly described the translational potential of learned safety by examining the impact of safety signals on human anxiety and found that safety signals were able to reduce anticipatory anxiety as revealed by a FPS paradigm (Grillon et al, 1994b).…”
Section: Translational Aspects and Potential Applications In Clinicalmentioning
confidence: 99%
“…Already in the 1990s, pioneering work by Christian Grillon and Michael Davis firstly described the translational potential of learned safety by examining the impact of safety signals on human anxiety and found that safety signals were able to reduce anticipatory anxiety as revealed by a FPS paradigm (Grillon et al, 1994b). This seminal study is of great importance considering the translational value of the FPS response, a most commonly used parameter for fear in human fear-conditioning paradigms.…”
Section: Translational Aspects and Potential Applications In Clinicalmentioning
confidence: 99%
“…Anomalies in fear learning, such as failure to inhibit fear to safety signals (CS 2 ), lead to sustained, generalized anxiety, 3,14,24,45 which in turn may augment pain. 43,49 Moreover, a meta-analysis on fear conditioning studies 39 and recent experimental findings 20,28,34,41 suggest that pathological anxiety is associated with impaired inhibition rather than disproportionate fear to danger signals (CS 1 ).…”
Section: Introductionmentioning
confidence: 99%